2013
DOI: 10.4103/0028-3886.115060
|View full text |Cite
|
Sign up to set email alerts
|

Are syncopes in sitting and supine positions different? Body positions and syncope: A study of 111 patients

Abstract: Against common belief, syncope can occur in sitting as well as in supine position. Emotional triggers were commoner in patients with syncope in supine and sitting positions while prodromal symptoms and circumstances were similar for all positions. Syncope should be considered in body positions other than standing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 9 publications
(16 reference statements)
2
30
0
1
Order By: Relevance
“…In studies dealing with typical VVS, syncope occurring in the horizontal position was observed in only 5% of subjects and was always triggered by emotional distress 3 29. When syncope occurs in the supine position, a cardiac cause of syncope should first be considered; if a cardiac cause is excluded, other examinations, chosen on the basis of the clinical presentation, should be performed.…”
Section: Syncope During Sleeping Hoursmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies dealing with typical VVS, syncope occurring in the horizontal position was observed in only 5% of subjects and was always triggered by emotional distress 3 29. When syncope occurs in the supine position, a cardiac cause of syncope should first be considered; if a cardiac cause is excluded, other examinations, chosen on the basis of the clinical presentation, should be performed.…”
Section: Syncope During Sleeping Hoursmentioning
confidence: 99%
“…The possible underlying mechanisms include the circadian-modulated increase in parasympathetic nervous activity, decreased sympathetic nervous system activity, decreased systolic blood pressure and decreased cardiac output during the night. As some subjects have reported nightmares immediately before sleep syncope,29 some episodes might actually be emotional VVS. Sleep syncope can be diagnosed in the presence of typical autonomic prodromes and in the absence of structural heart disease or primary electrical disease.…”
Section: Syncope During Sleeping Hoursmentioning
confidence: 99%
“…Syncope is defined as a transient loss of consciousness due to cerebral hypoperfusion with recovery being spontaneous and instantaneous [1-2]. It is a common ailment that forms 3% of emergency admissions and 1% of general hospital admissions [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent literature now supports the hypothesis that both vagally mediated hypotension and cardioinhibition can be noted while in a supine position. Several reports of supine loss of consciousness, which was determined to be vagal in mechanism, have been reported in the literature [1,11-13], and in 2006, a study named this phenomenon “sleep syncope” or “sleep fainting” and suggested it as a new clinical entity [14]. Furthermore, this phenomenon is not an uncommon observation in hospital settings in which the patient is supine, such as while venepuncture is performed and vagal symptoms are noted [15].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical clue is that sitting intolerance symptoms were observed in clinical practice, such as dizziness, palpitations, chest tightness, etc. elicited by sitting and relieved by recumbence 8,9 . Therefore, in children and adolescents, abnormal changes in heart rate and blood pressure might sometimes occur during sitting or the postural change from supine to sitting and be ambiguously associated with sitting intolerance which means that subjects are disturbed by the abovementioned symptoms during sitting or changing from supine to sitting.…”
mentioning
confidence: 99%